Design of refinery hydrogen recycling networks using enhanced genetic algorithm - Aviso, Kathleen B. (Animo Repository, 2007)
In any industry, the efficient utilization of resources brings about economic and environmental benefits. Refineries use hydrogen-consuming and hydrogen-generating processes to convert crude feedstocks into petroleum-based products. Thus, they require the efficient utilization and management of hydrogen. Obtaining the optimum hydrogen-recycling network requires matching available hydrogen sources with hydrogen sinks under constraints of stream quality, quantity and economics. The problem can be formulated as a multi-constraint knapsack problem. This paper explores the application of a modified genetic algorithm as an optimization technique to solve such a problem. Results show that the algorithm is capable of efficiently finding the model solution.